2021
DOI: 10.3389/fneur.2021.713124
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics-Based Approach to Identify Novel Blood Biomarker Candidates for Differentiating Intracerebral Hemorrhage From Ischemic Stroke—A Pilot Study

Abstract: Background: A reliable distinction between ischemic stroke (IS) and intracerebral hemorrhage (ICH) is required for diagnosis-specific treatment and effective secondary prevention in patients with stroke. However, in resource-limited settings brain imaging, which is the current diagnostic gold standard for this purpose, is not always available in time. Hence, an easily accessible and broadly applicable blood biomarker-based diagnostic test differing stroke subtypes would be desirable. Using an explorative prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 131 publications
1
16
1
Order By: Relevance
“…The stroke subjects were recruited within an average of 7 days (1–15 days) of symptom onset. Only two proteins (ITIH3 and LBP) were commonly differentially expressed in our study when compared to Malicek et al ( 9 ). Another proteomic study conducted by Allard et al ( 23 ) in plasma samples utilized the SELDI approach and identified four differentially expressed proteins (Apo C-1, Apo C-III, serum amyloid A, and antithrombin-III fragment) between 21 total stroke (IS = 11, ICH = 10) and 21 healthy controls recruited within 72 h. Of these four proteins, serum amyloid A was also differentially expressed in our study and was significantly downregulated in total stroke (fold change= 0.26) compared to the control group.…”
Section: Discussioncontrasting
confidence: 48%
See 4 more Smart Citations
“…The stroke subjects were recruited within an average of 7 days (1–15 days) of symptom onset. Only two proteins (ITIH3 and LBP) were commonly differentially expressed in our study when compared to Malicek et al ( 9 ). Another proteomic study conducted by Allard et al ( 23 ) in plasma samples utilized the SELDI approach and identified four differentially expressed proteins (Apo C-1, Apo C-III, serum amyloid A, and antithrombin-III fragment) between 21 total stroke (IS = 11, ICH = 10) and 21 healthy controls recruited within 72 h. Of these four proteins, serum amyloid A was also differentially expressed in our study and was significantly downregulated in total stroke (fold change= 0.26) compared to the control group.…”
Section: Discussioncontrasting
confidence: 48%
“…No protein was commonly expressed upon comparing their results with our study. The difference in the protein expression profile between our studies could be attributed to the small sample size and longer blood sample collection time in the Malicek et al study (9). Another recent study by Lee et al (7) on serum samples used a similar approach of discovery-based SWATH-MS proteomics and identified 163 differential proteins with more than 2-fold change in 20 IS patients recruited within 10 days of symptom onset compared to 20 healthy controls.…”
Section: S Nomentioning
confidence: 62%
See 3 more Smart Citations